Cooperation south - United Nations Development Programme (New York, N.Y. : United Nations Development Programme, 1985)
The magazine of technical co-operation among developing countries
Title from cover.
"The magazine of technical co-operation among developing countries, TCDC."
oif 27/07/16
Periodical
Keywords: Technology; Technology and state; Technical assistance; Technische samenwerking